Phytochemical Screening and In Silico Analysis of Some Crude Stem Extracts against Skin Diseases - Dubey, Surbhi; Sao, Shweta (International Journal of Computer Sciences and Engineering, 2025)
Curcumin is an important phytochemical present in curcuminoids (rhizome plants) essential; for control of skin diseases. The phytochemicals are more in Zingiber officinale followed by Aloe barbadensis, Curcuma longa and Curcuma angustifolia. Amino acids, Proteins, carbohydrates, tanins and terpenoids were almost present in all the selected plants. The plant Curcuma angustifolia aqueous extract has good composition of terpinoids and analysed for in silico studies of Curcumin with Staphylococcus aureus, Streptococcus pyogenes and Trichophyton rubrum proteins. Curcumin has shown good binding affinity with streptococcal superantigen (SSA) from Streptococcus pyogenes (-90.62 KCal/Mol) followed by exfoliative toxin B in Staphylococcus aureus (-85.01 KCal/Mol) and Aspartate Semialdehyde Dehydrogenase from Trichophyton rubrum (82.96 KCal/Mol). Curcumin has shown good in silico activities against proteins/ antigens for skin diseases. Further isolation and identification through wetlab studies provide good scope in the field of phytochemistry